ACTIVITIES IN TEACHING THE SPEAKING SKILL TO THE STUDENTS WITH VISION IMPAIRMENT - Safitri, Asri (2013)
This study entitled "Activities in Teaching the Speaking Skill to the Students with Vision Impairment" is aimed at investigating the variety of speaking activities conducted by the teacher and students' responses to the implementation of those activities. This study employed a qualitative research design and a case study approach. The data were collected through observations, interview and questionnaires where the participants were an English teacher and students with vision impairment. To analyze the data, Thornburry's (2005) categories of classroom speaking activities were used. The findings reveal that there were five kinds of speaking activities conducted by the teacher within four weeks; drilling, dictation, conversation and chat, guessing games, and word-cued task. Regarding the students' responses, there were positive responses of the students toward English, speaking skill and the activities conducted by the teacher. This study, therefore, suggests that future researcher should conduct similar research involving more participants in higher and lower grade as well as more time to gain more details of activities in teaching speaking. Keywords: students with vision impairment, speaking activities, students' responses.